The prevalence of Middle East respiratory Syndrome coronavirus (MERS-CoV) infection in livestock and temporal relation to locations and seasons - Samy Kasem; Ibrahim Qasim; Ali Al-Doweriej; Osman Hashim; Ali Alkarar; Ali Abu-Obeida; Mohamed Saleh; Ali Al-Hofufi; Hussein Al-Ghadier; Raed Hussien; Ali AL-Sahaf; Faisal Bayoumi; et al. (Elsevier, 2018)
Background: The Middle East respiratory syndrome (MERS) has been reported for the first time infecting a human being since 2012. The WHO was notified of 27 countries have reported cases of MERS, the majority of these cases occur in the Arabian Peninsula, particularly in Saudi Arabia. Dromedary camels are likely to be the main source of Middle East respiratory syndrome virus (MERS-CoV) infection in humans. Methods: MERS-CoV infection rates among camels in livestock markets and slaughterhouses were investigated in Saudi Arabia. A total of 698 nasal swabs were collected and examined with Rapid assay and rtRT-PCR. Ten MERS-CoV positive samples were subjected to full genomic sequencing. In addition, the sensitivity and specificity of the Rapid immunochromatographic assay (BioNote, South Korea) was evaluated as a diagnostic tool for MERS-CoV compared to rtRT-PCR. Results: The results showed a high percentage of dromedaries (56.4%) had evidence for nasal MERS-CoV infection. Phylogenetic analysis of the ten MERS-CoV isolates showed that the sequences were closely related to the other MERS-CoV strains recovered from camels and human cases. Moreover, the results showed that 195 samples were positive for MERS-CoV by rapid assay compared to 394 positive samples of rtRT-PCR, which showed low rapid assay sensitivity (49.49%) while, the specificity were found to be 100%. Conclusion: These findings indicate that these sites are a highly-hazardous to zoonotic diseases. Keywords: MERS, Slaughterhouses, Livestock markets, Saudi Arabia